Empowerment of the Community through Coffee Brownies Production Training Based on the Local Potential of Karanganyar Village - Tadqiroh, Alfiatun; Ferdianzah, Triyogi; Fitria, Nesy; Purnomo, Andhika Dwi; Anggraeni, Vira Eka; Santoso, Febri; Susilowati, Dini; Putra, Tendi Novendra; Aurelia, Rizka Putri; Nisrina, Dhiya; Salsabila, Sadira Rafa; Fauziridwan, Meydy; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
Karanganyar Village is one of the coffee production centers in Banjarnegara Regency; however, the utilization of coffee by the community is still limited to selling beans or powder, resulting in suboptimal added value for the commodity. This activity aims to empower the community through training in making coffee brownies as a processed product based on local potential, with the hope of creating opportunities for micro-scale culinary businesses. The training was conducted in August 2025 at the UMP 2025 KKN Post, using a participatory approach that involved residents from the preparation stage to the evaluation stage. The target participants were young people with the potential to develop coffee-based businesses. The implementation methods included a survey of local potential, hands-on practice in making coffee brownies, and an evaluation of the results. The outcomes showed that 85% of participants were able to independently make coffee brownies, and 40% of them expressed interest in reproducing the product as a home-based business. The training not only improved technical skills such as ingredient measurement and baking techniques but also raised awareness of the economic value of local coffee. This activity is recommended for replication in other villages with different local commodities to strengthen local potential-based economies.